Disaster governance and institutional dynamics in times of social-ecological change: Insights from New Zealand, the Netherlands and Greece. (November 2021) - Skrimizea, Eirini; Bakema, Melanie; McCann, Philip; Parra, Constanza
Abstract: In this paper, we engage with the 'good disaster governance' imperative and we attempt to empirically capture the (socio-)institutional dimensions and dynamics producing, reproducing or responding to social-ecological change and disasters. Viewing the disaster situation as a project of collective endeavour, we propose a conceptual framing of institutions building on disaster and development studies, governance of social-ecological systems, adaptive institutions research, and sociological institutionalist scholarship. We apply our analytical framework to Christchurch (New Zealand), Groningen (The Netherlands) and the island of Rhodes (Greece) through a relational comparative approach that builds on previous analyses and in-depth interviews with stakeholders. The three case-studies face diverse types of disasters that we conceptually approach around moments of 'abrupt change'. For Christchurch, the abrupt change refers to the earthquake of February 2011. For Groningen, it is a 'big' earthquake with a magnitude of 3.6 in 2012, and for Rhodes the intense water shortages or 'water crisis' in July 2017. The results reveal commonalities among the case studies around the crucial role institutions play in creating or exacerbating disasters; technical and structural challenges hindering institutions' adaptiveness; and institutional logics with lock-in effects leading to maladaptation. Our framing and discussion elucidate under-examined and under-theorized aspects of the 'adaptive governance' and 'adaptive institutions' concepts, and provides the basis for a socio-ecologically and socio-institutionally nuanced analytical approach to the pragmatics of disaster governance. Highlights: A social-ecological and sociological institutionalist lens to disaster governance Institutions accommodate or refuse pathways opening-up in disaster situations The mismatch in top-down/bottom-up practices restricts institutional adaptiveness Normative evaluation of disaster governance adaptive institutions is necessary